Reliability and validity of depression assessment among persons with HIV in sub-Saharan Africa: systematic review and meta-analysis - Tsai, Alexander C. (2014)
OBJECTIVES: To systematically review the reliability and validity of instruments used to screen for major depressive disorder or assess depression symptom severity among persons with HIV in sub-Saharan Africa. DESIGN: Systematic review and meta-analysis. METHODS: A systematic evidence search protocol was applied to seven bibliographic databases. Studies examining the reliability and/or validity of depression assessment tools were selected for inclusion if they were based on data collected from HIV-positive adults in any African member state of the United Nations. Random-effects meta-analysis was employed to calculate pooled estimates of depression prevalence. In a subgroup of studies of criterion-related validity, the bivariate random-effects model was used to calculate pooled estimates of sensitivity and specificity. RESULTS: Of 1,117 records initially identified, I included 13 studies of 5,373 persons with HIV in 7 sub-Saharan African countries. Reported estimates of Cronbach’s alpha ranged from 0.63–0.95, and analyses of internal structure generally confirmed the existence of a depression-like construct accounting for a substantial portion of variance. The pooled prevalence of probable depression was 29.5% (95% CI, 20.5–39.4), while the pooled prevalence of major depressive disorder was 13.9% (95% CI, 9.7–18.6). The Center for Epidemiologic Studies-Depression scale was the most frequently studied instrument, with a pooled sensitivity of 0.82 (95% CI, 0.73–0.87) for detecting major depressive disorder. CONCLUSIONS: Depression screening instruments yielded relatively high false positive rates. Overall, few studies described the reliability and/or validity of depression instruments in sub-Saharan Africa.